Aspekte Ungarischer Malerei der Gegenwart - Artbureau - Artex, Budapest; Erholungshaus der Bayer AG, Leverkusen; Stadthalle Hagen; Stadthaus-Galerie Münster (Leverkusen : KulturAbteilung Bayer AG, 1986)
Bak, Imre ; Birkas, Akos ; Borocz, Andras ; Erdély, Miklos ; Hencze, Tamas ; Keseru, Ilona ; Kovacs, Peter ; Mehes, Lorant ; Nadler, Istvan ; Piczehelyi, Sandor ; Revesz, Laszlo ; Rosko, Gabor ; Szirtes, Janos ; Tölg-Molnar, Zoltan ; Ujhazi, Peter ; Vetö, Janos
Aspekte Ungarischer Malerei der Gegenwart, Erholungshaus der Bayer AG, Leverkusen, 19. Oktober bis 23. November 1986 / Stadthalle Hagen, 12. bis 30. Januar 1987 / Stadthaus-Galerie Münster, April 1987
boek